Optimal control of cuk converter using LQR - Deepak Kumar Singh; Saibal Manna; Ashok Kumar Akella (Songklanakarin Journal of Science and Technology (SJST), 2023)
In this paper, linear quadratic regulator (LQR) control is applied to a Cuk converter, and mathematical modeling of the converter is done using state space averaging (SSA) in continuous conduction mode (CCM). The primary focus is to design a controller for the converter and maintain output voltage within 1% of the prescribed value when there is a unit step disturbance in the input. The design done by using MATLAB improved control of the converter from that with a conventional controller when tested with disturbances. The controller did not influence the system's stability, when assessed from the Bode plot. Despite the existence of disturbances, the findings prove the efficacy of the suggested approach, and the proposed controller can track the desired output voltage in less than 14 ms. The LQR control was developed for various applications of the Cuk converter, such as in a photovoltaic system and a wind system.